Uji Efektivitas Ekstrak Etanol 70% Daun Binahong (Anredera Cordifolia (Tenore.) Steenis) Terhadap Penurunan Kadar Ldl (Low Density Lipoprotein) Pada Tikus Putih Jantan Galur Wistar ( Rattus Norvegicus) Yang Diberi Pakan Hiperkolesterolemia Dan Diinduksi Triton X-100 - Pramastuti, Efi Dian; , Riandini Aisyah, S.Si, M. Sc (2017)
Background: Binahong leaves (Anredera cordifolia (Tenore.) Steenis) contain saponins that can reduce plasma cholesterol levels in two ways, inhibit cholesterol absorption in the intestine (direct) and inhibit the absorption of bile acids in the intestine (indirect). Blood plasma cholesterol levels, especially LDL are always used as an indicator to diagnose the possibility of heart problems due to atherosclerosis. Based on that, researcher was interested in studying about the efficacy test of 70% ethanol extract of binahong leaves(Anredera cordifolia (Tenore.) Steenis) on decreasing LDL level. Objective: To determine the effect of 70% ethanol extract of Binahong leaves(Anredera cordifolia (Tenore.) Steenis) on decreasing LDL level. Methods: This study is an experimental study with pre and post test method with control group design. The object of research were 25 male white rats (Rattus novergicus),150-200 g, 3-4 months and divided into 5 groups by simple random sampling technique, negative control (distilled water), positive control (Simvastatin 0.2 mg / 200gramBB / day) , treatment group dose I (5mg / kg / day), dose II (9mg / kg / day), and dose III (12mg / kg / day).LDL levels were measured before giving hypercholesterolemia feeding for 2 week and Tritton X-100 induced 3 day before measured, then LDL levels measured at day 14(pretest). The treatment was done on days 14-28, then levels of LDL measured at day 28 (posttest). The study was conducted for 28 days then the data were analyzed using paired t test and Kruskal-Wallis test followed by Mann-Whitney test Results:The 70% ethanol extract of Binahong leaves dose I (5mg / kg / day), dose II (9mg / kg / day), dose III (12mg / kg / day) have effect on decreasing LDL level with a mean decrease in a row is 35,42mg / dl, 22.19 mg / dl, 18,29mg / dl. The Kruskal-Wallis statistical tests showed p = 0.002 (p <0.05), so there was a significant difference in LDL levels between groups . Conclusion: 70% ethanol extract of Binahong leaves doses I, II, and III have effect on decreasing LDL level in white rats. Treatment group dose III had a potential effect on decreasing LDL level. Keywords: BinahongLeaf Extract, LDL, Rattus novergicus